The geology, copper-ore deposits and ground water hydrology of the area around Springbok and O'Okiep, Namaqualand - Strauss, C. A.(Christiaan Auret) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1941.